Sex differences in stroke and major adverse clinical events in patients with atrial fibrillation: A systematic review and meta-analysis of 993, 600 patients. (15th October 2018) - Marzona, Irene; Proietti, Marco; Farcomeni, Alessio; Romiti, Giulio Francesco; Romanazzi, Imma; Raparelli, Valeria; Basili, Stefania; Lip, Gregory Y.H.; Nobili, Alessandro; Roncaglioni, Maria Carla
Abstract: Background: Atrial fibrillation (AF) is the most commonly diagnosed arrhythmia, which is associated with an increased risk of stroke. Several studies have suggested that female AF patients could have a greater risk for stroke and thromboembolic events (TE). Methods: A systematic literature review update and meta-analysis was conducted using Pubmed. The search used the terms "atrial fibrillation", "gender", "sex", "female", "women", "stroke", "thromboembolism". Main aim of the study was to compare and male AF patients for occurrence of stroke and TE. Secondary outcomes were: major bleeding, cardiovascular (CV) death and all-cause death. Results: Forty-four studies were included in the analysis including 993, 603 patients (48.9% women). After pooling the data, there was a higher risk of stroke for women vs. male AF patients (hazard ratio [HR]: 1.24; 95% confidence intervals [CIs]: 1.14–1.36). Overall, TE risk was not different between female and male patients, despite sensitivity analysis left some uncertainties. No sex differences were found for major bleeding, CV death and all-cause death. A significant relationship between increasing age and the difference in stroke risk between female and male AF patients was found (Delta HR: 1.01; 95% CI: 1.00–1.03 for each year of age increase). Conclusions: Female patients with AF are at increased risk of stroke compared to men. A significant relationship between increasing age and stroke risk in women compared to men was found, most evident at age > 65 years. Female sex may act as a stroke risk modifier, particularly in elderly and very elderly AF subjects, conferring a significant increase in stroke risk. Highlights: Female AF patients have a significantly higher risk for stroke than male ones Stroke risk in female AF patients is significantly associated with increasing age Data suggest a possibly increased risk for thromboembolic events (TE) A higher risk for cardiovascular (CV) death in females is mediated by OAC use Data are needed to elucidate the role of female sex in TE and CV death in AF